Future directions for vaccine discovery 2 - Wilson, Chris (Henry Stewart Talks, 2015)
Pre-erythrocytic vaccine for falciparum malaria, Efficacy of RTS,S vaccine in humans, Genomic and functional analysis of cloned human antibodies, Improving acellular Pertussis vaccine (aP), New paradigm for vaccine development